Media and Messages for Nutrition and Health : Assessing Media Appropriateness for Nutrition and Health-Related Social and Behavior Change Communication in Four High Stunting-Burden Provinces of Lao PDR - Mbuya, Nkosinathi V.N.; Calleja, Ramon V., Jr.; Morimoto, Tomo; Thitsy, Sophavanh (World Bank, Washington, DC, 2020)
The Lao People’s Democratic Republic (Lao PDR) has experienced rapid and significant economic growth over the past decade. However, poor nutritional outcomes remain a concern. Rates of childhood undernutrition are particularly high in remote, rural, and upland areas. Media have the potential to play an important role in shaping health and nutrition–related behaviors and practices as well as in promoting sociocultural and economic development that might contribute to improved nutritional outcomes. This report presents the results of a media audit (MA) that was conducted to inform the development and production of mass media advocacy and communication strategies and materials with a focus on maternal and child health and nutrition that would reach the most people from the poorest communities in northern Lao PDR. Making more people aware of useful information, essential services and products and influencing them to use these effectively is the ultimate goal of mass media campaigns, and the MA measures the potential effectiveness of media efforts to reach this goal. The effectiveness of communication channels to deliver health and nutrition messages to target beneficiaries to ensure maximum reach and uptake can be viewed in terms of preferences, satisfaction, and trust. Overall, the four most accessed media channels for receiving information among communities in the study areas were village announcements, mobile phones, television, and out-of-home (OOH) media. Of the accessed media channels, the top three most preferred channels were village announcements (40 percent), television (26 percent), and mobile phones (19 percent). In terms of trust, village announcements were the most trusted source of information (64 percent), followed by mobile phones (14 percent) and television (11 percent). Hence of all the media channels, village announcements are the most preferred, have the most satisfied users, and are the most trusted source of information in study communities from four provinces in Lao PDR with some of the highest burden of childhood undernutrition.